Method for producing toner for developing electrostatic images

By using a crystalline polyester resin C and an amorphous resin A, combined with an open-roll type biscrew kneader for melt kneading, the method addresses the issue of poor low-temperature fixing and charging stability in toner production, achieving enhanced performance under high temperature and high humidity conditions.

JP7659456B2Active Publication Date: 2025-04-09KAO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021106994
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-28
Publication Date
2025-04-09
Estimated Expiration
2041-06-28

AI Technical Summary

Technical Problem

When producing a crushed toner using a crystalline polyester resin, insufficient dispersion of the crystalline polyester resin in the amorphous resin during melt kneading leads to poor low-temperature fixing characteristics, charging stability, and transferability, especially under high temperature and high humidity conditions.

Method used

A method for manufacturing a toner that involves using a crystalline polyester resin C, which is a polycondensate of ethylene glycol and an aliphatic dicarboxylic acid compound with 12 to 16 carbon atoms, combined with an amorphous resin A. The mixture is melted and kneaded using an open-roll type biscrew kneader to improve dispersibility and compatibility between the resin components.

Benefits of technology

The resulting toner exhibits excellent low-temperature fixing properties, electrical charge stability under high temperature and high humidity, and improved transferability, effectively addressing the limitations of previous toner manufacturing methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659456000001
    Figure 0007659456000001
  • Figure 0007659456000002
    Figure 0007659456000002
  • Figure 0007659456000003
    Figure 0007659456000003
Patent Text Reader

Abstract

To provide a method for manufacturing a toner for electrostatic charge image development which is excellent in low temperature fixability, charge stability under high temperature and high humidity and transferability.SOLUTION: A method for manufacturing a toner electrostatic charge image development contains a crystalline polyester resin C and an amorphous resin A, in which the crystalline polyester resin C is a polycondensation product of an alcohol component containing ethylene glycol and a carboxylic acid component containing an aliphatic dicarboxylic acid-based compound having 12 or more and 16 or less carbon atoms, and includes a step of melting and kneading a mixture containing the amorphous resin A and the crystalline polyester resin C using an open roll type biaxial kneader.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a toner for developing electrostatic images used in developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like. [Background technology]

[0002] It is known that a crystalline polyester resin is effective as a binder resin for a toner in improving the low-temperature fixing property of the toner, and its use in combination with an amorphous resin is being considered.

[0003] Patent Document 1 discloses a toner for developing electrostatic images, which contains an amorphous polyester resin A and a crystalline polyester resin C, in which the amorphous polyester resin A has a constituent portion derived from a polyester resin and a constituent portion derived from a modified polyolefin polymer A having a reactive functional group, the constituent portion derived from the polyester resin and the constituent portion derived from the modified polyolefin polymer A are linked via a covalent bond, and the amount of the constituent portion derived from the modified polyolefin polymer A is 5% by mass or more and 30% by mass or less with respect to the total amount of resin components in the toner.

[0004] Patent Document 2 discloses a binder resin composition for toners, which contains an amorphous polyester A and a crystalline polyester C, in which the amorphous polyester A is an amorphous polyester obtained by polycondensing an alcohol component containing an aromatic diol and an aliphatic diol having 3 to 6 carbon atoms and a carboxylic acid component, and the crystalline polyester C is a crystalline polyester obtained by polycondensing an alcohol component containing an aliphatic diol having 2 to 9 carbon atoms and a carboxylic acid component.

[0005] Patent Document 3 discloses an electrophotographic toner obtained by a method including a step of heating a mixture containing an amorphous polyester (A) obtained by polycondensing an alcohol component containing 60 mol % or more of an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom and a carboxylic acid component containing rosin and / or modified rosin, a crystalline polyester (B) having a number average molecular weight of 2,500 or more and 10,000 or less, and a polyester (C) having an isocyanate group, at a temperature in the range of 40° C. or more and 160° C. or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-86459 A [Patent Document 2] JP 2016-90628 A [Patent Document 3] JP 2016-53654 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, when producing a pulverized toner using a crystalline polyester resin, if the crystalline polyester resin is not sufficiently dispersed in the amorphous resin by melt kneading, the dispersibility will be insufficient even after it is cooled and made into a toner, so that the low-temperature fixability, which is a characteristic of the crystalline polyester resin, will not be fully exhibited, and the charging stability and transferability under high temperature and high humidity conditions will also be reduced, which still remains a problem.

[0008] The present invention relates to a method for producing a toner for developing electrostatic images, which has excellent low-temperature fixing properties, charge stability under high-temperature and high-humidity conditions, and transferability. [Means for solving the problem]

[0009] The present invention relates to a method for producing a toner for developing electrostatic images, which contains a crystalline polyester resin C and an amorphous resin A, the crystalline polyester resin C being a polycondensate of an alcohol component containing ethylene glycol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms, the method comprising a step of melt-kneading a mixture containing the amorphous resin A and the crystalline polyester resin C using an open-roll type twin-screw kneader. Effect of the Invention

[0010] The toner for developing electrostatic images obtained by the method of the present invention exhibits excellent effects in terms of low-temperature fixing property, charge stability under high-temperature and high-humidity conditions, and transferability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention has a major feature in that, when producing a toner for developing electrostatic images containing a crystalline polyester resin and an amorphous resin, the crystalline polyester resin is a polycondensate of raw material monomers containing specific monomers (ethylene glycol and an aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms) and an open roll type twin-screw kneader is used in the melt kneading step. The reason why the toner for developing electrostatic images obtained by the method of the present invention has excellent low-temperature fixing properties, charging stability under high temperature and high humidity conditions, and transferability is not clear, but is presumed to be as follows.

[0012] In the present invention, the dispersibility of the crystalline polyester resin in the amorphous resin is improved by using an open-roll type twin-screw kneader with high kneading strength and easy temperature control. In addition, since the crystalline polyester resin (crystalline polyester resin C) has ethylene glycol as an alcohol component, a hydrophilic portion is introduced into the crystalline polyester resin with improved dispersibility, so that the compatibility with the amorphous resin (amorphous resin A) is improved, the low-temperature fixability is improved, and the transferability is improved by improving the fluidity of the toner. In addition, since an aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms is contained as a carboxylic acid component, a hydrophobic portion is also introduced into the crystalline polyester resin, so that the compatibility with the amorphous resin is maintained, the moisture absorption of the toner is suppressed, and the charging stability under high temperature and high humidity is also excellent.

[0013] In the present invention, the crystalline polyester resin is a polycondensation product of an alcohol component containing ethylene glycol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms.

[0014] The crystallinity of a resin is represented by a crystallinity index defined as the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, i.e., the value of [softening point / maximum endothermic peak temperature]. A crystalline resin is a resin having a crystallinity index of 0.6 or more, preferably 0.7 or more, more preferably 0.9 or more, and 1.4 or less, preferably 1.2 or less, more preferably 1.1 or less. On the other hand, an amorphous resin is a resin in which no endothermic peak is observed, or if an endothermic peak is observed, the crystallinity index is greater than 1.4, preferably greater than 1.5, more preferably 1.6 or more, or less than 0.6, preferably 0.5 or less. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. In the case of a crystalline resin, the maximum endothermic peak temperature is the melting point.

[0015] From the viewpoint of low-temperature fixing property, the content of ethylene glycol in the alcohol component is preferably 70 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 100 mol %.

[0016] Examples of the alcohol component other than ethylene glycol include aliphatic diols other than ethylene glycol, such as 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol; aromatic diols, such as alkylene oxide adducts of bisphenol A; bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, and trimethylolpropane, and other trivalent or higher alcohols.

[0017] Examples of the aliphatic dicarboxylic acid compound include dodecanedioic acid (carbon number: 12), tetradecanedioic acid (carbon number: 14), succinic acid having an alkyl group or alkenyl group on the side chain, anhydrides of these acids, and alkyl esters of these acids having a carbon number of 1 to 3. Here, when the aliphatic dicarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.

[0018] The carbon number of the aliphatic dicarboxylic acid compound is 12 or more from the viewpoint of hydrophobicity, and is 16 or less, and preferably 14 or less, from the viewpoint of low-temperature fixability.

[0019] The content of the aliphatic dicarboxylic acid compound having 12 or more and 16 or less carbon atoms in the carboxylic acid component is, from the viewpoint of hydrophobicity, preferably 50 mol % or more, more preferably 60 mol % or more, even more preferably 70 mol % or more, and even more preferably 80 mol % or more, and is 100 mol % or less, preferably 98 mol % or less, and more preferably 95 mol % or less.

[0020] Other carboxylic acid components include aliphatic dicarboxylic acid compounds having 11 or less carbon atoms, such as succinic acid (carbon number: 4), fumaric acid (carbon number: 4), adipic acid (carbon number: 6), suberic acid (carbon number: 8), azelaic acid (carbon number: 9), and sebacic acid (carbon number: 10), aromatic dicarboxylic acid compounds, and trivalent or higher carboxylic acid compounds.

[0021] Furthermore, the alcohol component and / or the carboxylic acid component of the crystalline polyester resin C preferably contain a monofunctional monomer. From the viewpoint of improving hydrophobicity, the monofunctional monomer is preferably an aliphatic monofunctional monomer having 10 or more carbon atoms. Furthermore, from the viewpoint of reactivity, it is preferably a monofunctional monoalcohol or monocarboxylic acid.

[0022] Examples of monofunctional monomers contained in the alcohol component include aliphatic monoalcohols such as capric alcohol, lauryl alcohol, myristyl alcohol, palmityl alcohol, stearyl alcohol, and behenyl alcohol.

[0023] The carbon number of the aliphatic monoalcohol is preferably 10 or more, more preferably 12 or more, and even more preferably 14 or more from the viewpoint of hydrophobicity, and is preferably 22 or less, more preferably 20 or less, and even more preferably 18 or less from the viewpoint of low-temperature fixability.

[0024] Examples of monofunctional monomers contained in the carboxylic acid component include aliphatic monocarboxylic acids such as capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid, and aliphatic monocarboxylic acid compounds such as alkyl esters of these acids in which the alkyl group has 1 to 3 carbon atoms.

[0025] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monocarboxylic acid compound is preferably 10 or more, more preferably 12 or more, and even more preferably 14 or more, and from the viewpoint of low-temperature fixability, it is preferably 22 or less, more preferably 20 or less, and even more preferably 18 or less. Here, when the aliphatic monocarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.

[0026] The content of the monofunctional monomer in the raw material monomers (in the total amount of the alcohol component and the carboxylic acid component) is preferably 1 mol % or more, more preferably 3 mol % or more, and even more preferably 5 mol % or more, and from the viewpoint of low-temperature fixing property, it is preferably 30 mol % or less, more preferably 20 mol % or less, and even more preferably 15 mol % or less.

[0027] The equivalent ratio of the carboxylic acid component to the alcohol component (COOH group / OH group) is preferably 0.8 or more, more preferably 0.9 or more, from the viewpoint of storage stability, and is preferably 1.2 or less, more preferably 1.1 or less, from the viewpoint of low-temperature fixability.

[0028] The crystalline polyester resin C can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and if necessary, in the presence of an esterification promoter, a polymerization inhibitor, etc., at a temperature preferably of 120°C or higher and 230°C or lower.

[0029] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropylate bistriethanolamine. The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the esterification promoter include gallic acid. The amount of the esterification promoter used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the polymerization inhibitor include t-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.

[0030] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.

[0031] The softening point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher from the viewpoint of storage stability, and is preferably 120°C or lower, and more preferably 110°C or lower from the viewpoint of low-temperature fixability.

[0032] The melting point of the crystalline polyester resin C is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of storage stability, and is preferably 130° C. or lower, more preferably 120° C. or lower, from the viewpoint of low-temperature fixability.

[0033] The acid value of the crystalline polyester resin C is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, from the viewpoint of low-temperature fixability, and is preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, from the viewpoint of storage stability.

[0034] The content of crystalline polyester resin C in the total amount of crystalline polyester resin C and amorphous resin A is preferably 1 mass % or more, more preferably 3 mass % or more, and even more preferably 4 mass % or more from the viewpoint of low-temperature fixability, and is preferably 45 mass % or less, more preferably 40 mass % or less, more preferably 30 mass % or less, and even more preferably 20 mass % or less from the viewpoint of transfer efficiency.

[0035] Examples of the amorphous resin A include amorphous polyester resin, composite resin in which a polyester resin is combined with a styrene-based resin, polyamide resin, vinyl-based resin, epoxy resin, polycarbonate resin, polyurethane resin, and the like. In the present invention, from the viewpoint of improving transfer efficiency, an amorphous polyester resin or composite resin is preferred, and an amorphous polyester resin is more preferred.

[0036] As the amorphous polyester resin, a polycondensation product of an alcohol component containing an alkylene oxide adduct of bisphenol A and a carboxylic acid component is preferable.

[0037] Examples of the alkylene oxide adduct of bisphenol A include those represented by the formula (I):

[0038] [ka]

[0039] (In the formula, OR and RO are oxyalkylene groups, R is an ethylene group and / or a propylene group, x and y are the average number of moles of alkylene oxide added, each of which is a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less.) Preferred is a compound represented by the following formula:

[0040] From the viewpoint of low-temperature fixing ability, the content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 100 mol %.

[0041] Examples of other alcohol components include aliphatic diols, bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, trimethylolpropane and other trihydric or higher alcohols.

[0042] Examples of the carboxylic acid component include an aliphatic dicarboxylic acid compound, an aromatic dicarboxylic acid compound, and a trivalent or higher carboxylic acid compound.

[0043] Examples of the aliphatic dicarboxylic acid compound include fumaric acid, maleic acid, succinic acid, succinic acid derivatives substituted with a hydrocarbon group, glutaric acid, adipic acid, sebacic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0044] Examples of the aromatic dicarboxylic acid compound include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0045] Examples of the trivalent or higher carboxylic acid compound include trimellitic acid, pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0046] In the present invention, the carboxylic acid component of the amorphous polyester resin preferably contains a succinic acid derivative substituted with a hydrocarbon group, from the viewpoint of low-temperature fixability.

[0047] The hydrocarbon group in the succinic acid derivative substituted with a hydrocarbon group is preferably an alkyl group or an alkenyl group.Therefore, specific examples of the succinic acid derivative substituted with a hydrocarbon group include dodecylsuccinic acid, dodecenylsuccinic acid, tetrapropenylsuccinic acid, decenylsuccinic acid, their acid anhydrides, and their alkyl esters having 1 to 3 carbon atoms.Among these, from the viewpoint of low-temperature fixing property, dodecenylsuccinic acid, tetrapropenylsuccinic acid, or their acid anhydrides are preferred, and dodecenylsuccinic anhydride is more preferred.

[0048] From the viewpoint of hydrophobicity, the number of carbon atoms in the hydrocarbon group in the succinic acid derivative is preferably 8 or more, more preferably 10 or more, even more preferably 12 or more, and is preferably 20 or less, more preferably 18 or less, even more preferably 16 or less.

[0049] From the viewpoint of hydrophobicity, the succinic acid derivative preferably contains at least one or more types selected from the group consisting of succinic acid substituted with an alkyl group having from 10 to 18 carbon atoms and succinic acid substituted with an alkenyl group having from 10 to 18 carbon atoms, and more preferably contains at least one or more types selected from the group consisting of succinic acid substituted with an alkyl group having from 12 to 16 carbon atoms and succinic acid substituted with an alkenyl group having from 12 to 16 carbon atoms.

[0050] The content of the succinic acid derivative in the carboxylic acid component is preferably 1 mol% or more, more preferably 5 mol% or more, and even more preferably 7 mol% or more from the viewpoint of hydrophobicity, and is preferably 40 mol% or less, more preferably 30 mol% or less, even more preferably 20 mol% or less, and even more preferably 15 mol% or less from the viewpoint of storage stability.

[0051] The alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.

[0052] From the viewpoint of adjusting the softening point of the polyester resin, the equivalent ratio of the carboxylic acid component to the alcohol component (COOH group / OH group) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.75 or more, and is preferably 1.2 or less, more preferably 1.15 or less.

[0053] The polycondensation reaction conditions of the alcohol component and the carboxylic acid component of the amorphous polyester resin are similar to those of the crystalline polyester resin, except that the suitable reaction temperature is preferably 130°C or more, more preferably 170°C or more, and preferably 250°C or less, more preferably 240°C or less.

[0054] In the composite resin containing the polyester resin and the styrene-based resin, the polyester resin is the same as the amorphous polyester resin, and the styrene-based resin is an addition polymerization product of raw material monomers containing at least styrene or a styrene derivative such as α-methylstyrene or vinyltoluene (hereinafter, styrene and styrene derivatives are collectively referred to as "styrene compounds").

[0055] The content of the styrene compound, preferably styrene, in the raw material monomer of the styrene-based resin is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more from the viewpoint of storage stability, and is preferably 95% by mass or less, more preferably 93% by mass or less, and even more preferably 90% by mass or less from the viewpoint of low-temperature fixability.

[0056] The styrene-based resin may also contain, as a raw material monomer, an alkyl (meth)acrylate ester having an alkyl group with 7 or more carbon atoms. Examples of the alkyl (meth)acrylate ester include 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, and (iso)stearyl (meth)acrylate. It is preferable to use one or more of these. In this specification, "(iso)" means that both the case where this group is present and the case where it is not present are included, and when these groups are not present, it indicates that it is normal. Furthermore, "(meth)acrylic acid" refers to acrylic acid, methacrylic acid, or both.

[0057] From the viewpoint of improving the low-temperature fixing property of the toner, the number of carbon atoms in the alkyl group in the (meth)acrylic acid alkyl ester as a raw material monomer of the styrene-based resin is preferably 7 or more, more preferably 8 or more, and preferably 12 or less, more preferably 10 or less. The number of carbon atoms in the alkyl ester refers to the number of carbon atoms derived from the alcohol component constituting the ester.

[0058] The raw material monomers for the styrene-based resin may include raw material monomers other than styrene compounds and (meth)acrylic acid alkyl esters, for example, ethylenically unsaturated monoolefins such as ethylene and propylene; diolefins such as butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; ethylenic monocarboxylates such as dimethylaminoethyl (meth)acrylate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone.

[0059] The addition polymerization reaction of raw material monomers for the styrene-based resin can be carried out by a conventional method in the presence of a polymerization initiator such as dibutyl peroxide or dicumyl peroxide, a polymerization inhibitor, a crosslinking agent, or the like, in the presence of an organic solvent or without a solvent. The temperature conditions are preferably 110° C. or higher, more preferably 140° C. or higher, and preferably 200° C. or lower, more preferably 170° C. or lower.

[0060] When an organic solvent is used in the addition polymerization reaction, xylene, toluene, methyl ethyl ketone, acetone, etc. can be used. The amount of the organic solvent used is preferably 10 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the raw material monomer of the styrene-based resin.

[0061] The composite resin is preferably a resin in which a polyester resin and a styrene-based resin are bonded together, and more preferably a resin in which the polyester resin and the styrene-based resin are chemically bonded together via a bireactive monomer that can react with both the raw material monomers of the polyester resin and the raw material monomers of the styrene-based resin.

[0062] The bireactive monomer is preferably a compound having at least one functional group selected from the group consisting of hydroxyl group, carboxyl group, epoxy group, primary amino group and secondary amino group, preferably hydroxyl group and / or carboxyl group, more preferably carboxyl group and ethylenically unsaturated bond in the molecule, more preferably at least one selected from the group consisting of acrylic acid, methacrylic acid, fumaric acid, maleic acid and maleic anhydride, and from the viewpoint of reactivity of polycondensation reaction and addition polymerization reaction, still more preferably at least one selected from the group consisting of acrylic acid, methacrylic acid and fumaric acid. However, when used together with a polymerization inhibitor, a polyvalent carboxylic acid compound having an ethylenically unsaturated bond such as fumaric acid functions as a raw material monomer of polyester resin. In this case, fumaric acid etc. is not a bireactive monomer but a raw material monomer of polyester resin.

[0063] The amount of the bireactive monomer used is preferably 1 mol or more, and more preferably 2 mol or more, relative to 100 mol of the total of the alcohol components of the polyester resin, from the viewpoint of charging stability under high temperature and high humidity conditions, and is preferably 30 mol or less, more preferably 20 mol or less, and even more preferably 10 mol or less, from the viewpoint of increasing the dispersibility of the styrene resin and the polyester resin and improving the transferability of the toner. The amount of the bireactive monomer used is preferably 1 part by mass or more, more preferably 2 parts by mass or more, relative to 100 parts by mass of the raw material monomers of the styrene resin in terms of charging stability under high temperature and high humidity conditions, and is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, in terms of increasing the dispersibility of the styrene resin and the polyester resin and improving the transferability of the toner. Here, the polymerization initiator is included in the total amount of the raw material monomers of the styrene resin.

[0064] Specifically, the composite resin is preferably produced by the following method: When a bireactive monomer is used, the bireactive monomer is preferably used in an addition polymerization reaction together with a raw material monomer of a styrene-based resin from the viewpoint of improving the transferability of the toner and improving the low-temperature fixability and heat-resistant storage stability of the toner.

[0065] (i) A method in which a step (A) of polycondensation reaction of raw material monomers for a polyester resin is followed by a step (B) of addition polymerization reaction of raw material monomers for a styrene-based resin and a bireactive monomer. In this method, step (A) is carried out under reaction temperature conditions suitable for polycondensation reaction, and the reaction temperature is lowered to carry out step (B) under temperature conditions suitable for addition polymerization reaction. The raw material monomers of the styrene-based resin and the bireactive monomer are preferably added to the reaction system at a temperature suitable for the addition polymerization reaction. The bireactive monomer not only undergoes the addition polymerization reaction but also reacts with the polyester resin. After step (B), the reaction temperature is increased again, and if necessary, a raw material monomer of a polyester resin having a valence of 3 or more and serving as a crosslinking agent is added to the polymerization system, so that the polycondensation reaction of step (A) and the reaction with the bireactive monomer can be further promoted.

[0066] (ii) A method in which step (B) of an addition polymerization reaction of raw material monomers for a styrene-based resin and a bireactive monomer is followed by step (A) of a polycondensation reaction of raw material monomers for a polyester resin. In this method, step (B) is carried out under reaction temperature conditions suitable for an addition polymerization reaction, and then the reaction temperature is raised and the polycondensation reaction of step (A) is carried out under temperature conditions suitable for a polycondensation reaction. The bireactive monomer is involved in both the addition polymerization reaction and the polycondensation reaction. The raw material monomers of the polyester resin may be present in the reaction system during the addition polymerization reaction, or may be added to the reaction system under temperature conditions suitable for the polycondensation reaction. In the former case, the progress of the polycondensation reaction can be controlled by adding an esterification catalyst at a temperature suitable for the polycondensation reaction.

[0067] (iii) A method in which the reaction is carried out under conditions in which step (A) of polycondensation reaction of raw material monomers of a polyester resin and step (B) of addition polymerization reaction of raw material monomers of a styrene-based resin and a bireactive monomer proceed in parallel. In this method, it is preferable to carry out step (A) and step (B) in parallel under reaction temperature conditions suitable for addition polymerization reaction, raise the reaction temperature, add a raw material monomer of a polyester resin having a valence of 3 or more as a crosslinking agent to the polymerization system as necessary under temperature conditions suitable for polycondensation reaction, and further carry out the polycondensation reaction of step (A). In this case, under temperature conditions suitable for polycondensation reaction, a polymerization inhibitor can be added to proceed with only the polycondensation reaction. The bireactive monomer is involved in both the addition polymerization reaction and the polycondensation reaction.

[0068] In the above method (i), a prepolymerized polycondensation resin may be used instead of the step (A) in which a polycondensation reaction is carried out. In the above method (iii), when the reaction is carried out under conditions in which the steps (A) and (B) proceed in parallel, a mixture containing raw material monomers for a styrene resin may be dropped into a mixture containing raw material monomers for a polyester resin to carry out the reaction.

[0069] The above methods (i) to (iii) are preferably carried out in the same container.

[0070] The mass ratio of the polyester resin to the styrene resin in the composite resin (polyester resin / styrene resin) is preferably 98 / 2 or less, more preferably 95 / 5 or less, and even more preferably 90 / 10 or less from the viewpoint of charging stability under high temperature and high humidity, and is preferably 60 / 40 or more, more preferably 70 / 30 or more, and even more preferably 75 / 25 or more from the viewpoint of low temperature fixability. In the above calculation, the mass of the polyester resin is the amount obtained by subtracting the amount of reaction water (calculated value) dehydrated by the polycondensation reaction from the mass of the raw material monomer of the polyester resin used, and the amount of the bireactive monomer is included in the amount of raw material monomer of the polyester resin. In addition, the amount of the styrene resin is the total amount of the raw material monomer of the styrene resin and the polymerization initiator.

[0071] The softening point of the amorphous resin A is preferably 90° C. or higher, more preferably 100° C. or higher, from the viewpoint of storage stability, and is preferably 150° C. or lower, more preferably 140° C. or lower, from the viewpoint of low-temperature fixability.

[0072] From the viewpoints of low-temperature fixability and fixing width, the amorphous resin A may be composed of resins having different softening points. The difference in softening points between the two resins is preferably 10° C. or more, more preferably 12° C. or more, and is preferably 60° C. or less, more preferably 30° C. or less, and even more preferably 20° C. or less.

[0073] The softening point of the amorphous resin having the higher softening point (resin AH) is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher, from the viewpoint of fixing width, and is preferably 180°C or lower, more preferably 160°C or lower, and even more preferably 140°C or lower, from the viewpoint of low-temperature fixing ability.

[0074] Furthermore, the softening point of the amorphous resin having the lower softening point (resin AL) is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher from the viewpoint of storage stability, and is preferably 130°C or lower, more preferably 125°C or lower, and even more preferably 120°C or lower from the viewpoint of low-temperature fixability.

[0075] The mass ratio of resin AH to resin AL (resin AH / resin AL) is preferably 10 / 90 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less.

[0076] The glass transition temperature of the amorphous resin A is preferably 40° C. or higher, more preferably 50° C. or higher, from the viewpoint of storage stability, and is preferably 80° C. or lower, more preferably 70° C. or lower, and even more preferably 65° C. or lower, from the viewpoint of low-temperature fixability.

[0077] From the viewpoint of low-temperature fixing ability, the acid value of the amorphous resin A is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, and from the viewpoint of moisture absorption, it is preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less.

[0078] The number average molecular weight of the amorphous resin A is preferably 1,000 or more, more preferably 1,500 or more, and even more preferably 2,000 or more, from the viewpoint of moisture absorption, and is preferably 6,000 or less, more preferably 5,000 or less, and even more preferably 4,000 or less, from the viewpoint of low-temperature fixability.

[0079] The weight average molecular weight of the amorphous resin A is preferably 5,000 or more, more preferably 6,000 or more, and even more preferably 8,000 or more, from the viewpoint of moisture absorption, and is preferably 500,000 or less, more preferably 200,000 or less, and even more preferably 150,000 or less, from the viewpoint of low-temperature fixability.

[0080] The mass ratio of crystalline polyester resin C to amorphous resin A (crystalline polyester resin C / amorphous resin A) is preferably 1 / 99 or more, more preferably 3 / 97 or more, and even more preferably 5 / 95 or more from the viewpoint of low-temperature fixability, and is preferably 40 / 60 or less, more preferably 35 / 65 or less, and even more preferably 30 / 70 or less from the viewpoint of transfer efficiency.

[0081] In the toner, the crystalline polyester resin C and the amorphous resin A are contained as binder resins.

[0082] Other examples of the binder resin include vinyl resins such as styrene-acrylic resin, epoxy resin, polycarbonate, polyurethane, and composite resins containing two or more of these resins.

[0083] The total content of the crystalline polyester resin C and the amorphous resin A in the binder resin is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.

[0084] In addition, the content of the binder resin in the toner is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and is preferably less than 100% by mass, more preferably 98% by mass or less, even more preferably 95% by mass or less.

[0085] In addition to the binder resin, the toner may contain additives such as a colorant, a release agent, a charge control agent, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, and a cleaning property improver.

[0086] As the colorant, dyes, pigments, magnetic materials, etc. used as colorants for toners can be used. For example, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazo yellow, etc. can be mentioned. In the present invention, the toner may be either a black toner or a color toner.

[0087] From the viewpoint of improving the image density and low-temperature fixability of the toner, the content of the colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0088] Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.

[0089] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of transferability, and is preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 110° C. or lower, from the viewpoint of low-temperature fixability.

[0090] The content of the release agent is, from the viewpoint of low-temperature fixing property and transfer property of the toner and from the viewpoint of dispersibility in the binder resin, preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 1.5 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 7 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0091] The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.

[0092] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", and "Bontron N-11" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Kasei Corporation); and styrene-acrylic resins, such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Kasei Co., Ltd.).

[0093] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizenspiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (all manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE NX VP434 (Clariant), nitroimidazole derivatives, and organometallic compounds.

[0094] From the viewpoint of the charging stability of the toner, the content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0095] In the present invention, a mixture containing crystalline polyester resin C, amorphous resin A, and, if necessary, additives such as a colorant, a release agent, and a charge control agent, is subjected to a step of melt-kneading using an open-roll type twin-screw kneader.

[0096] The mixture to be melt-kneaded may be kneaded all at once or in portions, but it is preferable to mix the mixture in advance in a mixer such as a Henschel mixer or a ball mill and then supply the mixture to an open roll type twin-screw kneader.

[0097] The open-roll type twin-screw kneader is an extruder having two rolls, a melt-kneading section that is open and not sealed, and can easily dissipate the heat of kneading generated during melt-kneading. The open-roll type twin-screw kneader used in the present invention is provided with a plurality of raw material supply ports and kneaded material discharge ports provided along the axial direction of the rolls, and is preferably a continuous open-roll type twin-screw kneader from the viewpoint of production efficiency.

[0098] The open-roll type twin-screw kneader used in the present invention is preferably a kneader equipped with two rolls having different peripheral speeds, i.e., a high-speed roll having a high peripheral speed and a low-speed roll having a low peripheral speed. In the present invention, from the viewpoint of improving the dispersibility of the crystalline polyester resin, it is preferable that the high-speed roll is a heating roll and the low-speed roll is a cooling roll.

[0099] The temperature of the rolls can be adjusted, for example, by the temperature of a heat medium passed through the inside of the roll. Each roll may have its interior divided into two or more sections through which heat mediums of different temperatures are passed.

[0100] From the viewpoint of reducing the mechanical force during melt kneading and suppressing heat generation, the temperature of the raw material input side of the high rotation roll is preferably 80° C. or higher, more preferably 100° C. or higher, and even more preferably 120° C. or higher, and is preferably 160° C. or lower, and more preferably 150° C. or lower. From the same viewpoint, the temperature of the raw material input side of the low rotation roll is preferably 25° C. or higher, more preferably 40° C. or higher, and is preferably 80° C. or lower, and more preferably 70° C. or lower.

[0101] For both the high rotation roll and the low rotation roll, it is preferable that the temperature of the raw material input side is higher than that of the kneaded material discharge side, and the temperature difference between the raw material input side and the kneaded material discharge side is preferably 20°C or more, more preferably 30°C or more, from the viewpoint of preventing the kneaded material from detaching from the rolls and from the viewpoint of reducing the mechanical force during melt kneading and suppressing heat generation, and is preferably 60°C or less, more preferably 50°C or less.

[0102] The temperatures of the raw material inlet ends of the high rotation roll and low rotation roll refer to the set temperatures of the raw material inlet ends, and the temperatures of the kneaded material discharge ends refer to the set temperatures of the kneaded material discharge ends.

[0103] The peripheral speed of the high rotation roll is preferably 2 m / min or more, more preferably 10 m / min or more, even more preferably 25 m / min or more, and preferably 100 m / min or less, more preferably 75 m / min or less, and even more preferably 50 m / min or less, from the viewpoint of improving the dispersibility of the crystalline polyester resin, and from the viewpoint of reducing the mechanical force during melt kneading and suppressing heat generation. From the same viewpoint, the peripheral speed of the low rotation roll is preferably 1 m / min or more, more preferably 5 m / min or more, even more preferably 15 m / min or more, and preferably 90 m / min or less, more preferably 60 m / min or less, and even more preferably 30 m / min or less. In addition, the ratio of the peripheral speeds of the two rolls (low rotation roll / high rotation roll) is preferably 1 / 10 or more, more preferably 3 / 10 or more, and preferably 9 / 10 or less, more preferably 8 / 10 or less.

[0104] There are no particular limitations on the structure, size, material, etc. of each roll. The roll surface has grooves used for kneading, and the shape of these grooves may be linear, spiral, wavy, or uneven.

[0105] After the melt kneading, it is preferable to appropriately cool the kneaded product until it reaches a pulverizable hardness, and if necessary, toner particles are obtained by performing a pulverization step and classification. Here, cooling means cooling the kneaded product to 0°C or higher and 50°C or lower, or cooling to the glass transition temperature of the binder resin in the kneaded product or lower.

[0106] In pulverizing the kneaded product, the kneaded product may be pulverized to the desired particle size all at once or in stages. From the viewpoint of efficient and more uniform pulverization, however, it is preferable to perform the pulverization in two stages: coarse pulverization and fine pulverization.

[0107] Examples of the crushing machine used for the coarse crushing include a hammer mill, a cutter mill, an atomizer, and a rotoplex.

[0108] In the coarse pulverization, it is preferable to pulverize until the maximum diameter is 3 mm or less. For example, a pulverized material having a maximum diameter of 3 mm or less can be obtained by appropriately coarsely pulverizing the kneaded material until the particle size is about 0.05 mm or more and 3 mm or less, and then passing the kneaded material through a sieve with 3 mm openings.

[0109] Examples of the pulverizer used for fine pulverization include jet mills such as a fluidized bed jet mill and an impact plate jet mill, and mechanical mills.

[0110] The degree of pulverization is preferably adjusted appropriately depending on the desired particle size of the toner particles.

[0111] Examples of classifiers used for classification include airflow classifiers, inertial classifiers, sieve classifiers, etc. In the classification step, the pulverized material removed due to insufficient pulverization may be subjected to the pulverization step again, and the pulverization step and the classification step may be repeated as necessary.

[0112] In the present invention, it is preferable to further include an external addition step of mixing the obtained toner particles with an external additive.

[0113] Examples of the external additive include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as resin particles such as melamine-based resin fine particles and polytetrafluoroethylene resin fine particles, and two or more of them may be used in combination. Among these, silica is preferred, and from the viewpoint of the transferability of the toner, hydrophobic silica that has been subjected to a hydrophobic treatment is more preferred.

[0114] Examples of hydrophobic treatment agents for hydrophobizing the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.

[0115] From the viewpoints of the chargeability, fluidity, and transferability of the toner, the average particle size of the external additive is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.

[0116] From the viewpoint of the electrostatic chargeability, fluidity, and transferability of the toner, the content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner particles before being treated with the external additive, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.

[0117] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50 ) refers to the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size. In addition, when the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is regarded as the volume median particle size of the toner.

[0118] The toner obtained by the method of the present invention can be used as it is as a toner for one-component development, or as a toner for two-component development mixed with a carrier, in an image forming apparatus of a one-component development system or a two-component development system, respectively. EXAMPLES

[0119] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like can be measured by the following methods.

[0120] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The amount of plunger descent of the flow tester is plotted against the temperature, and the temperature at which half of the sample has flowed out is taken as the softening point.

[0121] [Maximum endothermic peak temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan, Inc.), weigh 0.01 to 0.02 g of sample into an aluminum pan, cool from room temperature (25°C) to 0°C at a rate of 10°C / min, and maintain at 0°C for 1 minute. Then, measure at a rate of 10°C / min. The temperature of the peak with the largest peak area among the observed endothermic peaks is regarded as the maximum endothermic peak temperature.

[0122] [Glass transition temperature of amorphous resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and cooled from that temperature at a rate of 10°C / min to 0°C. Next, the sample is heated at a rate of 10°C / min, and the endothermic peak is measured. The glass transition temperature is the temperature at the intersection of the extension of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak.

[0123] [Acid value of resin] Measurements are performed based on the method of JIS K 0070:1992, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K 0070 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)) for amorphous resins, and a mixture of chloroform and dimethylformamide (chloroform:dimethylformamide = 7:3 (volume ratio)) for crystalline resins.

[0124] [Number average molecular weight and weight average molecular weight of resin] The number average molecular weight and the weight average molecular weight are determined by gel permeation chromatography (GPC) according to the following method. (1) Preparation of sample solution The resin was dissolved in tetrahydrofuran to a concentration of 0.5 g / 100 mL, and the solution was then filtered using a fluororesin filter (manufactured by Sumitomo Electric Industries, Ltd., product name: FP-200) with a pore size of 2 μm to remove insoluble components, thereby obtaining a sample solution. (2) Molecular weight measurement Using the following measuring device and analytical column, tetrahydrofuran was used as the eluent at a flow rate of 1 mL per minute, and the column was stabilized in a thermostatic bath at 40°C. 100 μL of the sample solution was injected into the column and the measurement was performed. The molecular weight of the sample was calculated based on a calibration curve that had been prepared in advance. The calibration curve used here included several types of monodisperse polystyrene (Tosoh Corporation; 2.63 × 10 3 , 2.06×10 4 , 1.02×10 5 , GL Sciences Inc.; 2.10 x 10 3 , 7.00×10 3 , 5.04×10 4 ) is used as a standard sample. Measuring device: CO-8010 (product name, manufactured by Tosoh Corporation) Analytical column: GMH XL +G3000H XL (All are product names, manufactured by Tosoh Corporation)

[0125] [Melting point of release agent] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan, Inc.), 0.02 g of the sample is weighed into an aluminum pan and heated to 200°C, then cooled from 200°C to 0°C at a rate of 10°C / min. The sample is then heated at a rate of 10°C / min, the amount of heat is measured, and the maximum endothermic peak temperature is taken as the melting point.

[0126] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average of major and minor diameters) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these by number.

[0127] [Volume median particle size of toner (D 50 )〕 Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" (manufactured by Kao Corporation, HLB (Griffin) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured, and the volume median particle size (D 50 ) is required.

[0128] Preparation of alkenyl succinic anhydride 1 (1) Propylene tetramer (manufactured by Nippon Oil Corporation, product name: "Light Tetramer") was used and fractionated under heating conditions of 183 to 208°C to obtain an alkylene compound (a). The obtained alkylene compound (a) had 40 peaks in gas chromatography mass spectrometry described below. The distribution of the alkylene compounds was measured according to the analysis of alkylene compound A by mass spectrometry gas chromatography in JP 2014-013384 A, and the C9H 18 :0.5% by mass, C 10 H20 :4% by mass, C 11 H 22 :20% by mass, C 12 H 24 :66% by mass, C 13 H 26 :9% by mass, C 14 H 28 : 0.5% by mass (6 peaks corresponding to alkylene compounds having 9 to 14 carbon atoms).

[0129] (2) 542.4 g of alkylene compound (a), 157.2 g of maleic anhydride, 0.4 g of antioxidant "Chelex-O" (SC Organic Chemical Co., Ltd., Triisooctyl phosphite), and 0.1 g of butyl hydroquinone as a polymerization inhibitor were charged into a 1 L autoclave manufactured by Nitto Koatsu Co., Ltd., and pressurized nitrogen replacement (0.2 MPaG) was repeated three times. After stirring was started at 60 ° C, the temperature was raised to 230 ° C over 1 hour and the reaction was carried out for 6 hours. The pressure when the reaction temperature was reached was 0.3 MPaG. After the reaction was completed, the mixture was cooled to 80 ° C, returned to normal pressure (101.3 kPa), and transferred to a 1 L four-neck flask. The mixture was heated to 180 ° C with stirring, and the remaining alkylene compound was distilled off at 1.3 kPa for 1 hour. Subsequently, the mixture was cooled to room temperature (25° C.) and then returned to normal pressure (101.3 kPa) to obtain 406.1 g of the target product, alkenyl succinic anhydride A. The average molecular weight of alkenyl succinic anhydride A calculated from the acid value was 268.

[0130] Resin manufacturing example 1 The alcohol component and carboxylic acid component shown in Table 1 were placed in a 5-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. Then, an esterification catalyst was added, and the reaction was carried out at 8.0 kPa until the softening point shown in Table 1 was reached, obtaining crystalline polyester resins (resins C1 to C8). The physical properties are shown in Table 1.

[0131] [Table 1]

[0132] Resin manufacturing example 2 The raw material monomers of polyester resin other than trimellitic anhydride, esterification catalyst and esterification promoter shown in Table 2 were placed in a 5-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and then polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 210°C, trimellitic anhydride was added, and the reaction was carried out at 210°C for 1 hour, and then the reaction was further carried out at 210°C under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, to obtain an amorphous polyester resin (resin AH1). The physical properties are shown in Table 2.

[0133] Resin manufacturing example 3 The raw material monomers of polyester resin other than trimellitic anhydride and fumaric acid shown in Table 2, the esterification catalyst and the esterification promoter were placed in a 5-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and then polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 160°C, and a mixture of the bireactive monomer, the raw material monomer of the styrene resin and the polymerization initiator was dropped over 1 hour using a dropping funnel. After the dropping, the addition polymerization reaction was matured for 1 hour while maintaining the temperature at 160°C, and then the temperature was raised to 200°C and reduced pressure at 10 kPa for 1 hour. After opening the pressure, the temperature was lowered to 180°C, and the trimellitic anhydride, fumaric acid and polymerization inhibitor shown in Table 2 were added, and the temperature was kept at 180°C for 1 hour, and then the temperature was raised from 180°C to 210°C at 10°C / h, and the reaction was carried out at 210°C for 1 hour. Furthermore, the reaction was continued at 210° C. under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, to obtain an amorphous composite resin (Resin AH2).

[0134] Resin manufacturing example 4 The raw material monomers of polyester resin other than trimellitic anhydride and fumaric acid shown in Table 2, esterification catalyst and esterification promoter were placed in a 5-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and heated to 235 ° C under a nitrogen atmosphere, and then polycondensed at 235 ° C for 6 hours. The temperature was then lowered to 180 ° C, trimellitic anhydride, fumaric acid and a polymerization inhibitor were added, and the mixture was kept at 180 ° C for 1 hour, and then heated from 180 ° C to 210 ° C at 10 ° C / h, and reacted at 210 ° C for 1 hour. Furthermore, the reaction was carried out at 210 ° C under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, and an amorphous polyester resin (resin AH3) was obtained. The physical properties are shown in Table 2.

[0135] Resin manufacturing example 5 The raw material monomers, esterification catalyst and esterification promoter for the polyester resin shown in Table 2 were placed in a 5-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, followed by polycondensation at 235°C for 6 hours. The temperature was then lowered to 210°C, and the reaction was continued under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, yielding amorphous polyester resins (resins AL1 and AL3). The physical properties are shown in the table.

[0136] Resin manufacturing example 6 The raw material monomers of polyester resin other than fumaric acid shown in Table 2, the esterification catalyst and the esterification promoter were placed in a 5-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and then polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 160°C, and a mixture of the bireactive monomer, the raw material monomers of the styrene resin and the polymerization initiator was dropped over 1 hour using a dropping funnel. After the dropping, the addition polymerization reaction was matured for 1 hour while maintaining the temperature at 160°C, and then the temperature was raised to 200°C and reduced pressure at 10 kPa for 1 hour. After opening the pressure, the temperature was lowered to 180°C, and the fumaric acid and polymerization inhibitor shown in Table 2 were added, and the mixture was kept at 180°C for 1 hour, and then the temperature was raised from 180°C to 210°C at 10°C / h, and the reaction was carried out at 210°C for 1 hour. Furthermore, the reaction was continued at 210° C. under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, to obtain an amorphous composite resin (Resin AL2).

[0137] [Table 2]

[0138] Examples 1 to 10 and Comparative Examples 2 to 4 100 parts by mass of the binder resin shown in Table 3, 5 parts by mass of a colorant "ECB-301" (manufactured by Dainichi Seika Chemicals Co., Ltd., phthalocyanine blue (PB15:3)), 3 parts by mass of a release agent "Carnauba Wax C1" (manufactured by Kato Yoko Co., Ltd., melting point: 83°C), 3 parts by mass of a release agent "HNP-9" (manufactured by Nippon Seiro Co., Ltd., paraffin wax, melting point: 75°C), and 0.5 parts by mass of a charge control agent "Bontron E-304" (manufactured by Orient Chemical Co., Ltd.) were mixed in a Henschel mixer.

[0139] The obtained raw material mixture was fed to a continuous open-roll type twin-screw kneader "Kneedex" (manufactured by Mitsui Mining Co., Ltd.) by a table feeder and kneaded to obtain a kneaded product. The continuous open-roll type twin-screw kneader used here had a roll outer diameter of 0.14 m and an effective roll length of 0.8 m, and the operating conditions were a rotation speed of the high rotation roll (front roll) of 75 r / min (circumferential speed 33 m / min), a rotation speed of the low rotation roll (rear roll) of 50 r / min (circumferential speed 22 m / min), and a roll gap of 0.1 mm. The heating and cooling medium temperatures in the rolls were set to 140°C on the raw material inlet side of the high rotation roll, 110°C on the kneaded product discharge side, 65°C on the raw material inlet side of the low rotation roll, and 30°C on the kneaded product discharge side. The supply speed of the raw material mixture was 10 kg / h, and the average residence time was about 5 minutes.

[0140] The resulting kneaded product was cooled to 25°C and coarsely pulverized using a pulverizer "Rotoplex" (manufactured by Toa Machinery Co., Ltd.) and a coarsely pulverized product with a particle size of 2 mm or less was obtained using a sieve with a mesh size of 2 mm. Fine pulverization and upper limit classification (removal of coarse powder) were performed using a counter jet mill "400AFG" (manufactured by Hosokawa Alpine Co., Ltd.). Furthermore, lower limit classification (removal of fine powder) was performed using a classifier "TTSP" (manufactured by Hosokawa Alpine Co., Ltd.) to obtain toner particles with a volume median particle size of 6.5 μm.

[0141] 100 parts by mass of the obtained toner particles and, as external additives, 1.0 part by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) were mixed in a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 3000 r / min (circumferential speed: 32 m / sec) for 3 minutes to obtain a toner.

[0142] Comparative Example 1 A toner was obtained in the same manner as in Example 1, except that the melt-kneading was performed using a co-rotating twin-screw extruder "PCM-30" (manufactured by Ikegai Corporation) instead of a continuous open-roll type twin-screw kneader, with a screw rotation speed of 200 r / min and a barrel set temperature of 100° C. to obtain a melt-kneaded product. The feed rate of the mixture during melt-kneading was 20 kg / h, and the average residence time was about 18 seconds.

[0143] Test Example 1 [Low temperature fixability] The toner was mounted on a copy machine "AR-505" (manufactured by Sharp Corporation) whose fixing unit was modified to enable fixing outside the machine, and a printout was obtained in an unfixed state (print area: 2 cm × 12 cm, adhesion amount: 0.5 mg / cm 2 ). Then, using a fixing machine (fixing speed 300 mm / sec) adjusted to a total fixing pressure of 40 kgf, the temperature of the fixing roll was raised from 100°C to 200°C in 5°C increments, and a fixing test was performed on the unfixed printed matter at each temperature. A cellophane adhesive tape "UNICEF Cellophane" (manufactured by Mitsubishi Pencil Co., Ltd., width: 18 mm, JIS Z1522:2009) was attached to the image portion of the obtained printed matter, and the printed matter was passed through a fixing roller set to 30°C, which was separate from the fixing roll of the fixing machine, and then the tape was peeled off. The optical reflection density before and after the tape was attached and peeled off was measured using a reflection densitometer "RD-915" (manufactured by GretagMacbeth), and the temperature of the fixing roll at which the ratio of the two (after peeling / before attachment x 100) first exceeded 90% was determined as the minimum fixing temperature. The results are shown in Table 3. The lower the minimum fixing temperature, the better the low-temperature fixing property. The fixing paper was "CopyBond SF-70NA" (Sharp Corporation, 75 g / m 2 ) was used.

[0144] Test Example 2 [Charge stability under high temperature and high humidity (HH)] Under high temperature and humidity conditions of 32°C and 85%, 0.6 g of toner and 19.4 g of silicone ferrite carrier (Kanto Denka Kogyo Co., Ltd., average particle size 90 μm) were placed in a 50 mL polyethylene container and mixed at 250 rpm using a ball mill. The charge amount of the toner was measured using a Q / M meter (EPPING) according to the following method. After a certain mixing time, a specified amount of the toner and carrier mixture was put into a cell attached to the Q / M meter, and only the toner was sucked through a sieve with 32 μm openings (stainless steel, twill weave, wire diameter: 0.0035 mm) for 90 seconds. The voltage change on the carrier that occurred at that time was monitored, and the value of [total amount of electricity after 90 seconds (μC) / amount of sucked toner (g)] was taken as the charge amount (μC / g). The ratio of the charge amount after 60 seconds of mixing to the charge amount after 600 seconds of mixing (charge amount after 60 seconds of mixing / charge amount after 600 seconds of mixing) was calculated to evaluate the charge stability. The results are shown in Table 3. The larger the value, the better the charge stability under high temperature and high humidity conditions.

[0145] Test Example 3 [Transferability] The toner was loaded into a color printer "MICROLINE 5400" (product name, manufactured by Oki Data Corporation) and a solid image was printed. At this time, the amount of toner on the photoconductor for the solid image was 0.40 to 0.50 mg / cm. 2 The machine was stopped midway through printing a solid image, mending tape was applied to the photoconductor after it had passed the transfer section, and the toner remaining on the photoconductor without being transferred was transferred to the mending tape, and the mending tape was then peeled off from the photoconductor. The hue difference between the peeled off mending tape and an unused mending tape was measured using a color difference meter "X-Rite" (product name, manufactured by X-Rite Corporation), and the transferability was evaluated based on the color difference density (ΔE). The results are shown in Table 3. A smaller value indicates better transferability.

[0146] [Table 3]

[0147] From the above results, it can be seen that, compared with Comparative Example 1 in which a twin-screw extruder was used instead of an open-roll type twin-screw kneader, and Comparative Examples 2 to 4 in which a crystalline polyester resin not using a desired raw material monomer was used, Examples 1 to 10 provide toners with good low-temperature fixing properties and excellent charging stability and transferability under high-temperature and high-humidity conditions. In particular, a comparison between Examples 1, 6, and 7 and Example 8 reveals that the use of a crystalline polyester resin obtained using a monofunctional monomer significantly improves the charge stability and transferability in particular. On the other hand, a comparison between Comparative Example 2 and Comparative Example 3 reveals that when sebacic acid having 10 carbon atoms is used as the carboxylic acid component of the crystalline polyester resin, the charge stability and transferability are almost unchanged even when a monofunctional monomer is used in combination, and that the effect of the monofunctional monomer is due to its combination with a specific aliphatic dicarboxylic acid compound. [Industrial Applicability]

[0148] The toner for developing electrostatic images obtained by the method of the present invention is suitably used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like.

Claims

1. 1. A method for producing a toner for developing electrostatic images, comprising: a crystalline polyester resin C and an amorphous resin A; the crystalline polyester resin C is a polycondensate of an alcohol component containing ethylene glycol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms; the method comprises a step of melt-kneading a mixture containing the amorphous resin A and the crystalline polyester resin C using an open-roll type twin-screw kneader; the amorphous resin A is an amorphous polyester resin or an amorphous composite resin in which a polyester resin is bonded to a styrene-based resin; and the aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms is at least one selected from the group consisting of dodecanedioic acid, tetradecanedioic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

2. The method according to claim 1 , wherein the content of the crystalline polyester resin C is 3% by mass or more and 40% by mass or less in the total amount of the crystalline polyester resin C and the amorphous resin A.

3. The method according to claim 1 or 2, wherein the alcohol component and / or the carboxylic acid component of the crystalline polyester resin C contains a monofunctional monomer.

Citation Information

Patent Citations

  • Electrophotographic toner

    JP2016053654A

  • Toner binder resin composition

    JP2016090628A

  • Toner for electrostatic charge image development

    JP2020086459A